Multifunctional block copolymer nanocarriers for co-delivery of silver nanoparticles and curcumin: Synthesis and enhanced efficacy against tumor cells. (August 2016) - Petrov, Petar D.; Yoncheva, Krassimira; Gancheva, Valeria; Konstantinov, Spiro; Trzebicka, Barbara
Graphical abstract: Highlights: Multilayer nanocarriers are formed via self-assembly of a triblock terpolymer. Two anti-cancer agents are loaded within the multilayer nanocarriers. Co-delivery of silver nanoparticles and curcumin increased the cytotoxic activity. Abstract: Functional multilayer polymeric micelles were obtained by self-assembly of a poly(ethylene oxide)- b -poly( n -butyl acrylate)- b -poly(acrylic acid) (PEO113 - b -PnBA235 - b -PAA14 ) triblock terpolymer and exploited as template for the synthesis of silver nanoparticles and loading of anti-cancer agents. The terpolymer was synthesized by atom transfer radical polymerization of n -butyl acrylate and tert -butyl acrylate (tBA), initiated by a PEO-based macroinitiator. Then, PtBA blocks were converted into PAA by selective hydrolysis. PEO113 - b -PnBA235 - b -PAA14 terpolymer formed nano-sized spherical micelles in the concentration range from 1 to 10 mg mL −1 as confirmed by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The presence of PAA chains in the middle micellar layer allowed loading of silver ions and subsequent UV-induced synthesis of silver nanoparticles within the micelles. After that, the anti-cancer drug curcumin was loaded in the hydrophobic PnBA micellar cores. The effect of combination of two anti-cancer agents, spontaneously released from the micelles, on the vitality of acute myeloid leukemia (HL-60), its multidrug-resistant subline HL-60/DOX and human urinary bladder carcinoma (EJ) cells was assessed. The in vitro experiments revealed enhanced efficacy in regard to the cytotoxic activity of silver nanoparticles and curcumin.